SHORT COMMENT INDIA’S FIRST NATIONAL IPR POLICY: WHERE WE STAND - Mohit Madhav; Arpita Sinha (International Journal of Legal Developments & Allied Issues, 2016)
“Intellectual property, more than ever, is a line drawn around information, which asserts that despite having been set loose in the world - and having, inevitably, been created out of an individual’s relationship with the world - that information retains some connection with its author that allows that person some control over how it is replicated and used. - Nick Harkaway Intellectual Property Right is the right conferred upon the individual or organisation for his creation and innovations made by the application of his intellect in product or processes for a definite period of time. Like all other nations, India is also bestowed with bumper natural resources and Indians are blessed with sagacity, acumen, imagination, and brain power. Combination of these two results in various innovations in regards to comfort, requirement, and benefit. Earlier these innovations were common properties. Once after it came into existence its use was at the disposal of society at large. Nevertheless, with the passage of time, the efficacy of these innovations, creations were recognised and the need for intellectual property right was felt. Earlier, in 1994, the member countries of the world trade organisation entered into and signed the treaty on trade related aspects of intellectual property rights (TRIPS) which has formulated the norms for IPR on global basis. As a signatory to this TRIPS agreement India went on to introduce different legislations governing and regulating intellectual property in India. Different kinds of IP law in India are Trade Marks Act, 1999; Patents Act, 1970 (as amended in 2005); Copyright Act, 1957 (as amended in 2012); Designs Act, 2000; Geographical Indications of Goods (Registration and Protection) Act, 1999; Protection of Plant Varieties and Farmers’ Rights Act, 2001; Semiconductor Integrated Circuits Layout-Design Act, 2000 and Biological Diversity Act, 2002.